"It's real life, isn't it?" Integrated simulation teaching in undergraduate psychiatry education – a qualitative study. Issue 5 (12th August 2021) - Greenstone, Harriet; Wooding, Katie
Abstract : Purpose: High-fidelity simulation has well-established educational value. However, its use in psychiatry remains underexplored. This study explores medical students' experiences of high-fidelity simulation teaching during their psychiatry placements. A session was delivered on "psychiatric emergencies", set in a simulated emergency department, with equal emphasis on the management of physical and psychiatric aspects of patient care. This paper aims to report on student attitudes to high-fidelity simulation teaching in psychiatry, as well as student attitudes to "integrated" teaching (i.e. covering both physical and psychiatric knowledge). Design/methodology/approach: Semi-structured focus groups were conducted with medical students at a UK university. This exploratory approach generated rich qualitative data. Thematic analysis was used. Findings: High-fidelity simulation teaching in psychiatry is well regarded by medical students, and helps students recognise that psychiatric problems can present in any clinical setting. This study has demonstrated that students value this type of "integrated" teaching, and there is potential for this approach to be more widely adopted in undergraduate health-care professional education. High-fidelity simulation could also be considered for incorporation in undergraduate examinations. Originality/value: To the best of their knowledge, the authors are the first to conduct an in-depth exploration of attitudes to simulation teaching specifically in psychiatry. The authors are also the first to directly explore student attitudes to "integrated" teaching of psychiatry and physical health topics. The results will support the effective planning and delivery of simulation teaching in psychiatry, the planning of undergraduate summative assessments and will likely be of interest to health-care professionals, educational leads, simulation practitioners and students.